Settlement Planning and Urbanization: Theoretical Debates and Contested Issues - Sapkota, Mahendra (Geographical Journal of Nepal, 2025)
When discussing specific fields of study within urban studies, it is essential to look at settlement planning and urbanisation, which carry significant theoretical controversies regarding their socio-economic, environmental, and governance aspects. Following a systematic review method, this paper explores conceptual/theoretical literature navigating scientific issues and debates in the context of settlement planning and urban management. Environmental factors add another layer to this picture because fast-paced urban development kills off many natural structures and ecosystems. The article discusses various scholarly controversies related to these subjects and underlines the need for integrated and participatory approaches to settlement planning. The major findings of the study include that settlement planning is a basic process, which ensures that sustainable urbanisation is achieved through the proper planning and networking of the settlement. The study suggests that modern planning theories must adapt to the evolving dynamics of urbanization. More importantly, building and strengthening the interaction between policymakers, urban planners, and local communities can create a better tomorrow for the cities. Therefore, this review paper aims to contribute to the current debate in urban studies about appropriate planning principles and policies.